Parental Life Courses after Separation and Divorce in Europe - Kreyenfeld, Michaela; Trappe, Heike; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access book assembles landmark studies on divorce and separation in European countries, and how this affects the life of parents and children. It focuses on four major areas of post-separation lives, namely (1) economic conditions, (2) parent-child relationships, (3) parent and child well-being, and (4) health. Through studies from several European countries, the book showcases how legal regulations and social policies influence parental and child well-being after divorce and separation. It also illustrates how social policies are interwoven with the normative fabric of a country. For example, it is shown that father-child contact after separation is more intense in those countries which have adopted policies that encourage shared parenting. Correspondingly, countries that have adopted these regulations are at the forefront of more egalitarian gender role attitudes. Apart from a strong emphasis on the legal and social policy context, the studies in this volume adopt a longitudinal perspective and situate post-separation behaviour and well-being in the life course. The longitudinal perspective opens up new avenues for research to understand how behaviour and conditions prior or at divorce and separation affect later behaviour and well-being. As such this book is of special appeal to scholars of family research as well as to anyone interested in the role of divorce and separation in Europe in the 21st century.
Part I: Economic Conditions of Divorce and Separation: Chapter 1. Introduction: Parental Life Courses after Separation and Divorce in Europe -- Chapter 2. Economic Consequences of Divorce: A Review -- Chapter 3. Earnings Trajectories Following Parental Separation among First-Time Parents in Sweden -- Chapter 4. Changes in Mothers$1 (BEarnings around the Time of Divorce -- Chapter 5. Parents Returning to Parents: Does Migration Background Have an Influence on the (3z(BBoomerang Effect(3y (Bamong Parents after Divorce? -- Part II: Parent-Child Relationships: Chapter 6. Will Separations Lead to More or Less Gender-Equal Parenthood? Mothers$1 (Band Fathers$1 (BParental Leave Use in Sweden -- Chapter 7. Divorce, Emotions and Legal Regulations: Shared Parenting in a Climate of Fear -- Chapter 8. The Consequences of Separation for Mothers$1 (BPerception of their Parenting Capacity -- Chapter 9. The Role of Gatekeeping in Non-Resident Fathers$1 (BContact with their Children: Mothers$1 (Band Fathers$1 (BViews -- Part III: Parentand Child Well-being -- Chapter 10. Loneliness in Children Adapting to Dual Family Life -- Chapter 11. Paternal Psychological Well-being after Union Dissolution: Does Involved Fatherhood have a Protective Effect? -- Chapter 12. Gender Differences in Parental Well-being after Separation: Does Shared Parenting Matter? -- Part IV: Health-related Consequences of Divorce and Separation -- Chapter 13. Heterogeneous Effects of Family Complexity in Childhood on Mental Health: Testing the (3z(BGood Divorce(3y (Band the (3z(BGood Stepparent(3y (BHypotheses -- Chapter 14. Work Disability and Divorce.s
Keywords: Life cycle, Human; Population -- Economic aspects; Quality of life; Sociology; Social groups; Europe -- Politics and government; Life Course; Population Economics; Quality of Life Research; Sociology of Family, Youth and Aging; European Politics